Analysis of the Influence of Government Expenditures in the Education, Health and Infrastructure Sectors on Economic Growth in Lampung Province - Tarisa Yuwan Azzahra; Ambya Ambya (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This research aims to analyze the influence of government spending in the education, health and infrastructure sectors on economic growth in Lampung Province in 2014 - 2021. The analytical method used in this research is panel data regression analysis with the help of Eviews software. Statistical tests used in this research include classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), t test, f test, and coefficient of determination test. The results of this research show that: (1) government spending in the education sector partially has a positive and significant effect on economic growth in Lampung Province, (2) government spending in the health sector partially has a positive and significant effect on economic growth in Lampung Province, (3) spending government infrastructure sector partially has a positive and significant effect on economic growth in Lampung Province, (4) government spending in the education, health and infrastructure sectors simultaneously or together has a significant effect on economic growth in Lampung Province.